Big Data aplicada a la segmentación publicitaria (Meta Ads) y su impacto gerencial: caso Electrohogar - Balseca Mejia, Cristopher Johao (Machala : Universidad Técnica de Machala, 2025)
This study analyzes the impact of advertising segmentation in Meta Ads, based on Big Data, on managerial decision-making and commercial performance at the Ecuadorian home appliances company Electrohogar. Using a mixed-method approach, quantitative data from segmented advertising campaigns (January–April 2025) was combined with a review of recent literature (2020–2025). The results show a significant increase in online sales, with monthly growth rates of up to 290% compared to 2024, demonstrating that segmentation by interests, location, and purchasing behavior optimizes advertising budget use and increases return on investment. The discussion compared these findings with similar studies, confirming that personalization based on Big Data improves conversion rates and customer loyalty. The study concludes that the strategic use of Meta Ads, complemented by real-time adjustments, enables adaptation to market dynamics and sustains competitive advantages. It is recommended that Electrohogar continue strengthening this strategy and integrate it with tools such as CRM to enhance personalization and the effectiveness of future campaigns.
Este estudio analiza el impacto de la segmentación publicitaria en Meta Ads, basada en Big Data, en la toma de decisiones gerenciales y el rendimiento comercial de la empresa ecuatoriana de electrodomésticos Electrohogar. Con un enfoque mixto, se combinaron datos cuantitativos obtenidos de campañas publicitarias segmentadas (enero–abril 2025) con revisión de literatura reciente (2020–2025). Los resultados muestran un incremento significativo en las ventas online, con crecimientos mensuales de hasta el 290 % respecto a 2024, evidenciando que la segmentación por intereses, ubicación y comportamiento de compra optimiza el uso del presupuesto publicitario y eleva el retorno de inversión. La discusión comparó estos hallazgos con estudios similares, confirmando que la personalización basada en Big Data mejora la conversión y la fidelización del cliente. Se concluye que el uso estratégico de Meta Ads, complementado con ajustes en tiempo real, permite adaptarse a las dinámicas del mercado y sostener ventajas competitivas. Se recomienda a Electrohogar continuar fortaleciendo esta estrategia e integrarla con herramientas como CRM para potenciar la personalización y eficacia de futuras campañas.
Keywords: TOMA DE DECISIONES; BIG DATA; SEGMENTACIÓN; META ADS